Dyke-Davidoff-Masson Syndrome: A Case Report (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background : Dyke-Davidoff-Masson Syndrome (DDMS) is a rare neurological disorder that results from brain injury in intrauterine or early years of life. This condition is characterised by hemicerebral atrophy/hypoplasia secondary to brain insult and is accompanied by ipsilateral compensatory osseous hypertrophy and contralateral hemiparesis.Case Presentation : Here we describe about a 17 months old female child who presented with unable to stand or walk without support till date and left sided weakness since birth. Neurological examination revealed left-sided spastic hemiparesis with brisk tendon reflexes and equivocal planter response. MRI of brain revealed mild focal parenchymal volume loss in left superior parietal lobule with evidence of gliotic changes in the adjacent cerebral parenchyma. Left cranial fossa appeared to be smaller in size with slightly thickened skull bones and left lateral ventricular dilatation. Body and splenium of the corpus callosum was grossly hypoplastic. Focal parenchymal volume loss bordered by T2-flair hyperintensity was noted at right parieto-temporo-occipital region along with exvacuo dilatation of adjacent part of right lateral ventricle, suggesting encephalomalacic changes.Conclusion : As our patient presented with hemiparesis and developmental delay, her parents were counselled to take her to child development center for developmental therapy with regular follow up.Chatt Maa Shi Hosp Med Coll J; Vol.21 (2); July 2022; Page 64-66